Fireflies - Catherine Rich; Travis Longcore (Symphony in the Flint Hills, 2019)
Introduction: Fireflies may be expected to have inappropriate, innate responses to foreign light, similar to those that occur in other organisms. (Excerpted from: Ecological Consequences of Artificial Night Lighting, edited by Catherine Rich and Travis Longcore, published by Island Press, 2005.)